The development and validation of a patient-reported questionnaire to assess outcomes of elbow surgery. - Dawson, J; Doll, H; Boller, I; Fitzpatrick, R; Little, C; Rees, J; Jenkinson, C; Carr, A (2008)
We developed a questionnaire to assess patient-reported outcome after surgery of the elbow from interviews with patients. Initially, 17 possible items with five response options were included. A prospective study of 104 patients (107 elbow operations) was carried out to analyse the underlying factor structure, dimensionality, internal and test-retest reliability, construct validity and responsiveness of the questionnaire items. This was compared with the Mayo Elbow performance score clinical scale, the Disabilities of the Arm, Shoulder and Hand questionnaire, and the Short-Form (SF-36) General Health Survey. In total, five questions were considered inappropriate, which resulted in the final 12-item questionnaire, which has been referred to as the Oxford elbow score. This comprises three unidimensional domains, 'elbow function', 'pain' and 'social-psychological'; with each domain comprising four items with good measurement properties. This new 12-item Oxford elbow score is a valid measure of the outcome of surgery of the elbow.